The Effect of Coal and Sawdust Co-Firing on Boiler Efficiency with the Direct and Indirect Calculation Methods at PT PLN Nusantara Power Unit 2 - Issafira, Radissa Dzaky; Rizki, Muhammad Daru Fatkhur; Mokh Ausin Al Qoroni; Wardana, Vrischo Candra Kumara (Mechanical Engineering Department - Semarang State Polytechnic, 2025)
The increasing demand for electricity in Indonesia has led to a rise in fossil fuel consumption, resulting in negative environmental impacts. As part of its commitment to achieving net zero emissions by 2060, the Indonesian government has begun promoting the application of co-firing technology that utilizes biomass as an alternative fuel. One promising type of biomass is sawdust, which can be blended with coal in the combustion process. This study aims to analyze the effect of sawdust blending on boiler efficiency using both direct and indirect calculation methods. The results show that a fuel composition of 55% low-rank coal (LRC), 40% medium-rank coal (MRC), and 5% sawdust produces a boiler efficiency of 86.8% using the direct method and 85.2% using the indirect method. Additionally, this blend generates lower emissions compared to a mixture of 80% LRC and 20% MRC. These findings indicate that sawdust, when applied through co-firing technology, contributes to improved combustion efficiency and reduced emissions in coal-fired power plants.